Pengaruh Negative Customer Experience dan Alternative Attractiveness terhadap Switching Intention dengan Dissatisfaction sebagai Variabel Intervening pada Produk MS Glow - Isnawati Isnawati; Heriyadi Heriyadi; Wenny Pebrianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The Indonesian skincare industry is characterized by intense competition, making consumers highly sensitive to negative experiences and the attractiveness of alternative brands. This study aims to analyze the effect of negative customer experience and alternative attractiveness on switching intention, with dissatisfaction as an intervening variable among MS Glow consumers in Indonesia. A quantitative approach was employed using a survey method, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The sample consisted of MS Glow consumers who had used the products and experienced negative outcomes. The results indicate that negative customer experience and alternative attractiveness have a positive and significant effect on dissatisfaction. Furthermore, dissatisfaction has a positive and significant effect on switching intention. Both negative customer experience and alternative attractiveness also directly influence switching intention. Mediation analysis confirms that dissatisfaction plays a significant intervening role. These findings highlight the importance of managing customer experience and strengthening competitive advantages to reduce brand switching intentions in the local skincare industry.